Respuesta :

Answer:

-4 1/12

Step-by-step explanation:

Eliminating a negative and changing our operation.

=−213−134

Rewriting our equation with parts separated

=−2−13−1−34

Solving the whole number parts

−2−1=−3

Solving the fraction parts

−13−34=

Using improper fractions, the solution for the expression is:

[tex]-\frac{49}{12}[/tex]

-----------------------

The expression is given by:

[tex]-2\frac{1}{3} + (-1\frac{3}{4}) = -2\frac{1}{3} - 1\frac{3}{4}[/tex]

Converting the improper fractions to standard:

[tex]-2\frac{1}{3} = -2 - \frac{1}{3} = -\frac{6}{3} - \frac{1}{3} = -\frac{7}{3}[/tex]

[tex]-1\frac{3}{4} = -1 - \frac{3}{4} = -\frac{4}{4} - \frac{3}{4} = -\frac{7}{4}[/tex]

Solving the expression:

[tex]-2\frac{1}{3} - 1\frac{3}{4} = -\frac{7}{3} - \frac{7}{4} = -\frac{28 + 21}{12} = -\frac{49}{12}[/tex]

A similar problem is given at https://brainly.com/question/16725183